Implementation of Legal Protection in the Field of Pharmacy in a Juridical Review of the Implementation of Law Number 30 of 2000 Concerning Trade Secrets - Habib, Yahya Abdul; Erbiana, Nyi Mas Gianti Bingah (IJBLE Scientific Publications Community Inc., 2025)
The protection of trade secrets in the pharmaceutical sector is very important. Various trade secret crimes in the pharmaceutical sector, such as theft of drug prescriptions and counterfeiting of medicines, continue to increase. Another impact of trade secret crimes in the pharmaceutical sector is the medical risk of counterfeiting drugs consumed by the public. However, on the one hand, victims who have trade secret rights in the pharmaceutical sector are still few to report allegations related to trade secret violations. In addition, law enforcement has not been optimal in responding to every complaint from the public regarding the theft of drug prescriptions, counterfeiting of various pharmaceutical products, and complaints from trade secret rights owners. For this reason, the existence of Law Number 30 of 2000 concerning Trade Secrets should provide legal protection for every owner of trade secrets in the pharmaceutical sector and also the public who are victims of trade secret crimes in the pharmaceutical sector